The effect of shared decision-making for stroke prevention on treatment adherence and safety outcomes in patients with atrial fibrillation: a randomized clinical trial. (14th October 2021) - Noseworthy, P; Branda, M.E; Kunneman, M; Hargraves, I.G; Sivly, A.L; Brito, J.P; Burnett, B; Gorr, H; Suzuki, T; Lee, A.T; Jackson, E.A; Hess, E; et al.
Abstract: Background: Guidelines promote shared decision-making (SDM) for anticoagulation in patients with atrial fibrillation (AF). We recently showed that adding a within-encounter SDM tool to usual care (UC) increases patient involvement in decision making and clinician satisfaction, without affecting encounter length. Purpose: We aimed to estimate the extent to which use of an SDM tool affected patient adherence to the decided care plan and clinical safety endpoints. Methods: We conducted a multi-center, encounter-level randomized trial assessing the efficacy of UC with vs. without an SDM conversation tool for use during the clinical encounter (Anticoagulation Choice, AC) in patients with non-valvular AF considering starting or reviewing anticoagulation treatment. We conducted a chart and pharmacy review, blinded to randomization status, at 10 months post-enrollment to assess primary adherence (proportion of patients who were prescribed an anticoagulant who filled their first prescription) and secondary adherence (estimated using the proportion of days for which treatment was supplied and filled [PDC] for DOAC, and as time in therapeutic range (TTR) for warfarin). We also followed for any safety outcomes (stroke [stroke or transient ischemic attack], major bleeding, or death). Results: We enrolled 922 evaluable patient encounters (AC=463, UC=459), of which 814 (88%) had pharmacy and clinical follow-up. We found no differences between arms in either primary (78% of patients in AC filled their first prescription vs. 81% in UC) or secondary adherence to anticoagulation (see Figure, PDCDOAC was 74.1% in AC vs. 71.6% in UC; TTRwarfarin was 66.6% in AC vs. 64.4% in UC). PDCDOAC was better (65%) in AC than in UC (55%) (OR 1.49, CIs 1.00, 2.22). Safety outcomes, mostly bleeds, occurred in 13% (AC) of and 14% (UC) of participants. Conclusions: This is the largest reported randomized trial in AF comparing usual care with and without an SDM tool to promote SDM. Although patients were more actively involved in SDM, we found no significant differences between arms in primary or secondary adherence to anticoagulation or clinical safety outcomes. Funding Acknowledgement: Type of funding sources: Other. Main funding source(s): The trial was funded by and conducted independently of the National Heart, Lung, and Blood Institute (NHLBI) of the U.S. National Institutes of Health (RO1 HL131535-01). The funding body had no influence on the design and conduct of the study; collection, management, analysis, and interpretation of the data; preparation, review, or approval of the manuscript; and decision to submit the manuscript for publication.